2021
DOI: 10.1053/j.jvca.2021.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Survival After Extracorporeal Membrane Oxygenation for Severe COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 23 publications
3
77
1
Order By: Relevance
“…In case of severely ill COVID-19 patients, it has been found among 167 COVID-19 patients admitted to an intensive care unit (ICU) that older age and thrombocytopenia, among others, were significant risk factors for mortality at 28, 90 and 180 days [ 11 ]. Furthermore, in a multicentre-study from five European countries of hospitalized COVID-19 patients requiring extracorporeal membrane oxygenation (ECMO) showed that advanced age and low pH before ECMO were also associated with an increased risk of mortality within 6 months, with an overall rate of 53% (70/132) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In case of severely ill COVID-19 patients, it has been found among 167 COVID-19 patients admitted to an intensive care unit (ICU) that older age and thrombocytopenia, among others, were significant risk factors for mortality at 28, 90 and 180 days [ 11 ]. Furthermore, in a multicentre-study from five European countries of hospitalized COVID-19 patients requiring extracorporeal membrane oxygenation (ECMO) showed that advanced age and low pH before ECMO were also associated with an increased risk of mortality within 6 months, with an overall rate of 53% (70/132) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that QOL might worsen due to the development of CRDs after ECMO therapy, worsening long-term survival. We believe that our results are important because the number of ECMO survivors is bound to increase in the future due to the COVID-19 pandemic [ 22 ], and the QOL in ECMO survivors can be an important public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the oxygenation index was significantly lower in the ECMO group on admission (110 (IQR 90-161) vs. 178 (IQR 121-232), p = 0.009). Imaging on hospital admission showed a significantly higher severity score (21)(22) vs. 14 (IQR 10-19), p < 0.001) and significantly higher lung volume involvement (66% (IQR 49-72) vs. 30% (IQR 17-53), p < 0.001, Figure 3B) in the AI based CT assessment. Patients in the ECMO therapy group exhibited a significantly longer time interval from admission to the time point of maximum SOFA score (13 days (IQR 2-15) vs. 2 days (IQR 1-8) in the standard ICU therapy group, p = 0.012).…”
Section: Differences Between the Ecmo Group And Icu Standard Therapy Groupmentioning
confidence: 97%
“…In severe cases of COVID-19 with refractory hypoxemia the use of ECMO as a rescue therapy has been advocated [16][17][18]. Published ECMO mortality rates have ranged widely from around 40 to as high as 90% or above, whereas increasing evidence suggests that COVID-19 ECMO mortality might be similar to known ARDS ECMO mortality rates of around 40-60% and might not be significantly different to overall COVID-19 ICU mortality [2,8,12,[17][18][19][20][21][22][23]. Because ECMO therapy might reduce mortality and outcome is likely to improve when therapy is applied early in severe ARDS, early risk stratification and patient allocation is crucial [17,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%